Energy Consumption and Economic Growth in Indonesia - Dat, Nguyen Duy; Hoang, Nguyen; Huyen, Mai Thanh; Huy, Dinh Tran Ngoc; Lan, Luong Minh (International Journal of Energy Economics and Policy, 2020)
The aim of following study was to examine the relationship between energy consumption and economic growth in Indonesia. This study has used quantitative research design for assessing the energy consumption and its link with economic growth in Indonesia for the period of 2000-2019. The independent variable in this study was energy consumption whereas; dependent variable was economic growth in Indonesia .The data is analysed through E-views using Autoregressive Distributed Lag (ARDL) co-integration approach for long-run relationship, and long-run and short-run coefficients, Augmented Dickey Fuller (ADF) and Johansen co-integration. The findings have revealed that economic growth and energy consumption has association with each other. Within the given historic data, energy consumption has the ability to predict economic growth in Indonesia. The research can be improved through increasing sample size, number of variables and countries for comparison. This study also provides the guideline to the polcymakers that they should develop the policies related to the energy consumption that enhance the economic growth of the country. Keywords: Energy consumption, economic growth, GDP, CO2 emissions JEL Classifications: P18, O47 DOI: https://doi.org/10.32479/ijeep.10243